Pengaruh Profitabilitas, Ukuran Perusahaan, Nilai Perusahaan dan Debt to Equity Ratio Terhadap Return Saham Pada Perusahaan yang Terdaftar di BEI - Rieke Rahmalia; Suwarno Suwarno (Journal of Culture Accounting and Auditing, 2022)
This study aims to determine the effect of Profitability, Company Size, Firm Value, and Debt to Equity Ratio on Stock Returns in Companies Listed on the IDX. This study uses quantitative methods that use secondary data in the form of complete company financial statements. The sample in this study amounted to 50 samples of companies in the health, technology, transportation, and food and beverage sectors using purposive sampling technique. The data analysis technique used is using multiple linear regression with the help of SPSS 25 software. The results show that profitability (ROE) has no effect on stock returns, firm size (SIZE) affects firm returns, firm value (PBV) does not affect firm returns. , and the Debt to Equity Ratio (DER) has no effect on the company's return.